2014
DOI: 10.3748/wjg.v20.i35.12637
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for improved colonic anastomotic healing: A meta-analysis

Abstract: This systematic review identified only one randomized clinical trial and seven therapeutic agents from pre-clinical models that could be explored further for the prophylaxis of AL after colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 96 publications
0
46
0
1
Order By: Relevance
“…Studies have demonstrated many options and parameters to achieve the best results in intestinal healing. Animal models, surgical techniques, pharmaceutical interventions and different segments of GI tract have been tested and demonstrated different results 14,28 . Øines et al 28 in a recent meta-analysis identified seven therapeutic agents for improve the colonic anastomotic healing and that could be explored further.…”
Section: Strategies For Healing Improvement Of Colorectal Anastomosismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated many options and parameters to achieve the best results in intestinal healing. Animal models, surgical techniques, pharmaceutical interventions and different segments of GI tract have been tested and demonstrated different results 14,28 . Øines et al 28 in a recent meta-analysis identified seven therapeutic agents for improve the colonic anastomotic healing and that could be explored further.…”
Section: Strategies For Healing Improvement Of Colorectal Anastomosismentioning
confidence: 99%
“…Animal models, surgical techniques, pharmaceutical interventions and different segments of GI tract have been tested and demonstrated different results 14,28 . Øines et al 28 in a recent meta-analysis identified seven therapeutic agents for improve the colonic anastomotic healing and that could be explored further. They stratified the agents in four categories: immunomodulators, miscellaneous, proteinase inhibitors and growth hormone (GH) factors.…”
Section: Strategies For Healing Improvement Of Colorectal Anastomosismentioning
confidence: 99%
“…Furthermore, in the recently published guidelines of the European Society for Clinical Nutrition and Metabolism, teduglutide was considered the first choice for carefully selected patients with chronic intestinal failure who are candidates for growth factor treatment 8 . Several experimental studies, analyzing intestinal anastomotic repair-promoting methods, have suggested potential benefits from growth factors administration, including from insulin-like growth factor 1, epidermal growth factor, heparin-binding epidermal growth factor and fibroblast growth factor-7/ keratinocyte growth factor 9,10 , which have been considered mediators of the GLP-2 effects 1 . In fact, a recently published study demonstrated, through histological and immunohistochemical inflammatory and proliferative stages of the intestinal anastomotic repair 9,12 ), with ileal harvesting and blood collection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The development of post-operative anastomotic leak is one of the most concerning complications in colorectal resection surgery as it is associated with negative patient outcomes including increased risk of abscess or fistula development, greater incidence of infection or sepsis, prolonged hospital stays and a greater risk of post-operative mortality [2,[4][5][6][7]. Patients who experience anastomotic leak following colorectal resection surgery are also at an increased risk of cancer recurrence, impaired function of pelvic organs, and a permanent stoma [5,8].…”
Section: Introductionmentioning
confidence: 99%